Infancia y alfabetización mediática: Crítica, Práctica, Democracia - Cecilia Von Feilitzen (Doxa Comunicación, 2008)
The article points at main hindrances to media education and media literacy – for which many voices have propagated since long. Besides the urgent need for training of media educators, the conclusion is that most in need of media literacy are, in fact, the media themselves.